Jasin Smart Library / Alya Geogiana Buja … [et al.] - Geogiana Buja, Alya; Arshad, Mohamad Asrol; Md Rashid, Nor Aimuni; Azam, Nurul Alieyah (Faculty of Computer and Mathematical Sciences, 2022)
Smart libraries are known as digital, virtual, and intellectual libraries integrated with Information and Communication Technology. Nowadays, students are currently unimpressed with the manual shelves tagging in the library because it is difficult to read and time-consuming to find books, especially for students unfamiliar with manual shelves tagging. Jasin Smart Library mobile application have been developed and integrated with the Beacon technology. Using this application, the user will get the book menu when the mobile application sensed the signal emitted by the Beacon in the form of Bluetooth Low Energy (BLE). Each beacon signal is unique, and the information delivered is specified according to the Beacon. The application's effectiveness has been evaluated by conducting user acceptance and accuracy testing. For future work, make available on another operating system such as iOS, advanced searching and improve to make available in other places. In conclusion, Jasin Smart Library is useful and saves time consumption for any users to find book location in the big library without picking it out.